SPE Annual Technical Conference and Exhibition 1999
DOI: 10.2118/56813-ms
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Dependent Permeability: Characterization and Modeling

Abstract: During the production lifecycle of a reservoir, absolute permeability at any given location may change in response to an increase in the net effective stress and a concomitant decrease in the value of in-situ permeability. This paper focuses stress dependent permeability in unconsolidated, high porosity sand reservoirs (offshore turbidites) and consolidated reservoirs (tight gas sands). Specifically we address:fundamental controls on stress dependent permeability, as identified through analysis of core samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…For example, since an increase in the effective stress may cause a permeability and porosity reduction (Davies et al, 1999;Rutqvist et al, 2002), a drop in these hydrological parameters is expected where higher deformation are observed, namely at the centre of the domain and close to the fault zones. This may reduce the deformation and gravity change profiles over time.…”
Section: A Coco Et Al: Numerical Models For Ground Deformation and mentioning
confidence: 99%
“…For example, since an increase in the effective stress may cause a permeability and porosity reduction (Davies et al, 1999;Rutqvist et al, 2002), a drop in these hydrological parameters is expected where higher deformation are observed, namely at the centre of the domain and close to the fault zones. This may reduce the deformation and gravity change profiles over time.…”
Section: A Coco Et Al: Numerical Models For Ground Deformation and mentioning
confidence: 99%
“…The stress sensitivity of fractured gas reservoirs, in terms of their flow properties, has become a focus of much attention of research [11,12]. Permeability is well known to negatively correlate with the effective stress [13], and the stress-dependent permeability becomes the norm of petrophyiscal characterization for, but not limited to, fractured reservoirs [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Then, some researchers (Jones, 1975;Jones et al, 1980;Walsh, 1981;Randolph et al, 1984;Jelmert et al, 1998) established a mathematical relationship between core permeability and effective stress, and found that the formula is applicable to naturally fractured carbonated reservoir and low permeability sandstone reservoir. Davies et al (2001) compared the stress sensitivity characteristics of different permeability cores, and found that for unconsolidated cores with high permeability, the larger the porosity and permeability, the stronger the stress sensitivity. However, for some finely cemented cores with low permeability, the smaller the permeability, the stronger the stress sensitivity.…”
Section: Introductionmentioning
confidence: 99%